A Rough Neural Network Algorithm for multisensor Information Fusion - Xiaohui Chen (Institute of Advanced Engineering and Science, 2012)
The multisensor information fusion is a key issue for multisensor system. One of its difficulties lies in the switching of the state of sensor clusters. That is, which direction should the sensor information been fused into at a given moment? An algorithm of multisensor information fusion based on rough set and neural network was proposed in this paper. Firstly, the typical clustering distributions of 54 sensors within one day were regarded as sample space. The rough set was used for access of knowledge to make the decision table of the